PENGEMBANGAN MODUL PHOTOVOICE UNTUK MENINGKATKAN PENALARAN MORAL SISWA - Bertha Cyntia Angeline; Siti Muhibah; Alfiandy Warih Handoyo (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2021)
The research was motivated by moral problems that students of class XI of Bethel Kosambi HighÂ  School had. The aim of the research is to develop a module that can improve students' moral reasoning with photovoice techniques, in order to help BK teachers in dealing with students' moral problems. The method used in this study is research and development with the ADDIE model whose implications reach the development stage. As for the results of product feasibility tests from material experts with 75% content feasibility aspects, 75% presentation eligibility, 75% contextual feasibility, contextual eligibility 75% while media experts with 75% aspects of ability to graph. So that each total of each of these aspects is 75% which means that this guidebook is included in the criteria "WORTHY".Â